Novas paisagens e passagens da literatura brasileira contemporânea - Jefferson Agostini Mello; Ricardo Gonçalves Barreto (Estudos de Literatura Brasileira Contemporânea)
In this essay we will test the hypothesis that Brazilian literary fi eld is becoming more autonomous, i.e., more concerned to means of expression and to modifications operated in literary language, although it may still retain some marks of Realism, and although authors and critics disseminated fear of the economic market. In spite and because of this, the field creates aesthetical principles, forms of reception and strategies of prestige inside itself.